Post-transplant anemia in pediatric patients and its impact on patient and graft survival: single center experience - Gheith, Osama; Wafa, Ehab; Refaie, Ayman; Hassan, Nabil; Mostafa, Amani; Sheashaa, Hussein; Shokeir, Ahmaed; Kamal, Mohamed; Ghoneim, Mohamed A (African Journal of Nephrology, 2009)
<p style="margin: 4px; color: #000000; font-family: 'Merrieweather sans', sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">Introduction: Post-transplantation anemia (PTA)occurs frequently, with prevalence rates between 20and 60% depending on the criteria used for defininganemia. <p style="margin: 4px; color: #000000; font-family: 'Merrieweather sans', sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">Aim of the work: We aimed to assess the prevalenceof anemia after 6 months of transplantation inpediatric renal transplant patients under differentprotocols of immunosuppression, and to determinethe impact of anemia upon long-term patient andgraft survival. <p style="margin: 4px; color: #000000; font-family: 'Merrieweather sans', sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">Patients and methods: Based on the data of 108renal transplants performed in our center, patientswere categorized after 6 months according to theirhemoglobin (Hb) levels into two groups. The firstgroup with Hb more than 11gm/dl (group I, 29cases) and the second group with Hb lessthan11gm/dl (group II, 79cases). We compared thetwo groups regarding post transplant complications(rejection episodes, hypertension, diabetes mellitus,infections, hepatic dysfunction, and patient andgraft survival. <p style="margin: 4px; color: #000000; font-family: 'Merrieweather sans', sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">Results: we found no significant difference betweenthe two groups regarding rejection episodes.However, the percentage of cases with chronicallograft nephropathy was significantly higher in the anemic group. The survivors with functioning graftswere significantly higher in cases with normal Hb.Moreover, living cases with graft failure weresignificantly higher in anemic group. Graft survivalrate was better in the non anemic group. However,no difference in patient survival was detected. Also,we found no difference between the two groupsregarding post-transplant complications. <p style="margin: 4px; color: #000000; font-family: 'Merrieweather sans', sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">Conclusions: From this study, we can conclude thatthe prevalence of post-transplant anemia is highpediatric renal transplant patients especially thosereceiving CNI and MMF, and it was associated withpoorer graft outcome but no effect on patientsurvival.